CRISES OF YOUTH PERIODS - Murkhashev Akhmadkhan Olimjon ugli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
Therefore, the child’s biological growth is a factor that causes growth and changes in his psyche. But psychological changes do not always have proportionality with biological growth. Because, on the one hand, mental growth has the character of individuality, on the other hand, it directly depends on certain social and psychological conditions.